Evaluation of underground virtual environment training: Is a mining simulation or conventional power point more effective? - Zhang, S.; Stothard, Phillip; Kehoe, J. (SIMTECT, 2010)
UNSW’s Schools of Mining Engineering and Psychology have jointly developed high-fidelity simulations for training in the coal mining industry aimed at improving safety. These simulations have capitalised on advanced technology to move beyond replications of traditional class-room training and to implement best, evidence-based instructional practices. The present paper describes controlled experiments conducted as an initial, rigorous evaluation of the simulations by testing one small component. Specifically, a 3-D simulation of a coal mine was compared to a 2-D slide-based presentation in the acquisition, retention and transfer of a standardised operating procedure. Novices were trained to re-start an exhaust fan and were subsequently given a multiple-choice test immediately after training and then again after a retention interval of one week or more. In Experiment 1, training was conducted using the mining simulator (Group Sim) versus class-room slide presentations (Group PP).To maintain the participants’ active attention, each step of the procedure was followed by a question and feedback. Experiment 2 included a third condition in which participants in the mining simulator were asked to collaborate in generating answers to the in-training questions (Group Sim+). Two weeks after the retention test in Experiment 2, the top five participants in Groups Sim+ and PP provided a hands-on demonstration of the exhaust-fan procedure. Across experiments, training in the simulator tended to yield better test scores than the class-room training, particularly in the practical, hands-on test. The positive effect of the mine simulation on acquisition, retention, and transfer of the procedure provides a foundation for further simulation-based modules, which can replicated across mine sites and provide consistent training that does not depend on the individual trainer. This replication and consistency will decrease the cost of development and ownership to a small fraction of the cost of mining.